WAKAF UANG DALAM PERSPEKTIF HUKUM DAN POLITIK - Kencana, Ulya; Hadi, Abdul (Nurani, 2016)
Waqf money is a new concept of waqf law in Indonesia. Since legalized Act No. 41 of 2004 on Waqf, the Islamic community in Indonesia can give waqf money in Islamic Financial Institutions Endowments Money Receiver. Indonesian Waqf Board as the authorized state agencies to develop waqf in Indonesia has the authority to manage cash waqf. Indonesian Waqf Board has not been able to popularize the concept of cash waqf law in society. This corresponds to a legal political concern for the management of waqf money in Indonesia. Supposedly waqf money may provide the benefit of a sustainable society, for money as waqf objects could be productivity in business and generate profits and given to the public on an ongoing basis. This article eksplored the views of law and politics in the utilization of sustainable endowment fund.